2021
DOI: 10.3390/ph14060587
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of Influenza Virus Entry

Abstract: Hemagglutinin (HA) plays a critical role during influenza virus receptor binding and subsequent membrane fusion process, thus HA has become a promising drug target. For the past several decades, we and other researchers have discovered a series of HA inhibitors mainly targeting its fusion machinery. In this review, we summarize the advances in HA-targeted development of small molecule inhibitors. Moreover, we discuss the structural basis and mode of action of these inhibitors, and speculate upon future directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 98 publications
(159 reference statements)
1
28
0
Order By: Relevance
“…This function is due to a conformational rearrangement of the protein triggered by low pH. As already mentioned, several known ligands can bind a conserved region (stem) of the HA close to the fusion peptide [ 33 ]. The structural analysis of these ligands highlights the similarity of these compounds with our inhibitors ( Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This function is due to a conformational rearrangement of the protein triggered by low pH. As already mentioned, several known ligands can bind a conserved region (stem) of the HA close to the fusion peptide [ 33 ]. The structural analysis of these ligands highlights the similarity of these compounds with our inhibitors ( Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…The critical role played by this glycoprotein has prompted the development of antibodies directed toward the conserved stem region of HA to generate a universal vaccine [ 30 , 31 , 32 ]. Furthermore, many small molecules have been developed blocking the viral entry [ 33 ]. These latter can be important tools in Flu prevention and treatment as no FDA-approved therapy specifically blocks receptor binding or fusion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of the "compressed" or pre-fusion state by small molecules can prevent conformational transitions and both inhibit viral and cell membrane fusion. Some HA inhibitors work in a similar way [57], including Arbidol [58]. The presence of similar heptad repeats in HAs and S-protein suggests similar hydrophobic cavities (hydrophobic amino acids are shown by green spheres in Figure 6B) in the space between the spirals of the stem part of the protein.…”
Section: Elisa-based Competitive Inhibition Of the Rbd/ace2 Interactionmentioning
confidence: 95%
“…Pentacyclic triterpenoids are secondary plant metabolites found in various medicinal plants . Many previous works have revealed that pentacyclic triterpenoids and their derivatives have significant antiviral activity. In our previous study, an oleanolic acid ( OA ) derivative with galactose at position 17-COOH ( Y3 ) exhibited significant anti-influenza A/WSN/33 virus activity with an IC 50 value at the micromolar level by specific binding with hemagglutinin (HA) ( K D = 6.0 μM), the receptor binding and membrane fusion glycoprotein, and an up-and-coming target for anti-influenza virus drug discovery. , However, OA exerts no anti-influenza virus activity at high concentrations (IC 50 > 200 μM), although it retains moderate HA binding capacity, with a K D value of 34 μM . Thus, it could be an ideal molecule for the exploration of HA degradation by the PROTAC technology and could demonstrate proof in concept that targeted protein degradation may present a novel strategy for the design of new anti-influenza drugs (Figure ).…”
Section: Introductionmentioning
confidence: 99%